XMM-Newton observation of the very old pulsar J0108-1431 - Posselt, B.; Arumugasamy, P.; Pavlov, G.; Manchester, R.; Shannon, Ryan; Kargaltsev, O. (2012)
We report on an X-ray observation of the 166 Myr old radio pulsar J0108–1431 with XMM-Newton. The X-ray spectrum can be described by a power-law model with a relatively steep photon index Γ ≈ 3 or by a combination of thermal and non-thermal components, e.g., a power-law component with fixed photon index Γ = 2 plus a blackbody component with a temperature of kT = 0.11 keV. The two-component model appears more reasonable considering different estimates for the hydrogen column density N H. The non-thermal X-ray efficiency in the single power-law model is η PL1-10keV/E ~ 0.003, higher than in most other X-ray-detected pulsars. In the case of the combined model, the non-thermal and thermal X-ray efficiencies are even higher, η PL1-10keV ~ ηbbPC ~ 0.006. We detected X-ray pulsations at the radio period of P ≈ 0.808 s with significance of ≈7σ. The pulse shape in the folded X-ray light curve (0.15-2 keV) is asymmetric, with statistically significant contributions from up to five leading harmonics. Pulse profiles at two different energy ranges differ slightly: the profile is asymmetric at low energies, 0.15-1 keV, while at higher energies, 1-2 keV, it has a nearly sinusoidal shape. The radio pulse peak leads the 0.15-2 keV X-ray pulse peak by Δ ø = 0.06 ± 0.03.